Adaptation and ecosystem resilience of blue-green algae towards carotenogenesis regulatory mechanism - Othman, Rashidi; Abu Bakar, Ainaa Eliah; Mahmad, Noraini; Ahmad Fadzillah, Nurrulhidayah (2019)
Blue green algae (cyanobacteria) which known for its vibrant bluish green basically contains, phycocyanin, phycoerythrin and a number of yellow pigments, mainly carotenoids. The same species of blue green algae may vary in colour depending on the surrounding condition. The main issue that researcher want to address through this research is unclear mechanism regarding the pigmentation of blue-green algae towards its defense mechanism in certain degree of stress condition. In this research carotenoid biogenesis is investigated in blue green algae cell culture as a potential model system. The value of this experimental system for investigating variables controlling carotenoid accumulation is then tested by assessing the effects of environmental variables, such as drought stress, light intensity and nutrient strength on carotenoid accumulation. Our findings revealed that blue green algae pigmentation depending upon the spectral composition of the light. The lower the light intensity, the more accessory pigments effective in photosynthesis will be formed to catch a high percentage of the light. However, it was believed that it is beyond light intensity. It could be more key factors that can trigger blue green algae to change its colour accordingly to particular environment. Therefore, the necessity of this research is to develop a better understanding regarding blue-green algae (cyanobacteria) typologies and defensive behavior in different region. Anticipated benefits of the research may have potential in contributing to the defense/protective mechanism as well as ecological indicators in various fields in the future.